Strategies in Driving Learning Networks for Social Studies Teachers to Improve Educational Quality of Secondary Learners - Mangkhang, Charin (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018, 2018)
การวิจัยนี้มีจุดมุ่งหมายเพื่อ 1. วิเคราะห์บริบทที่หนุนเสริมในการสร้างเครือข่ายการเรียนรู้ของครูสังคมศึกษาในโรงเรียนมัธยมศึกษา 2. เสนอกลยุทธ์ขับเคลื่อนการสร้างเครือข่ายการเรียนรู้ของครูสังคมศึกษาเพื่อพัฒนาคุณภาพการศึกษาผู้เรียนในโรงเรียนมัธยมศึกษา และ 3. สร้างเครือข่ายการเรียนรู้ของครูสังคมศึกษาเพื่อพัฒนาคุณภาพการศึกษาผู้เรียนระดับมัธยมศึกษา การวิจัยนี้ใช้วิธีการวิจัยเชิงคุณภาพ กลุ่มเป้าหมายได้มาจากการเลือกแบบเจาะจงและมีความสมัครใจ จำนวน 37 คน ผลการวิจัย พบว่า 1. ผลการวิเคราะห์บริบทที่หนุนเสริมต่อการสร้างเครือข่ายการเรียนรู้ประกอบด้วย 3 ด้าน คือ 1) ด้านความพร้อมของเครือข่ายการเรียนรู้ 2) ด้านการจัดกิจกรรมของเครือข่าย และ 3) ด้านการบริหารจัดการเครือข่าย 2. กลยุทธ์ขับเคลื่อนการสร้างเครือข่ายการเรียนรู้ ประกอบด้วย 5 กิจกรรม ได้แก่ 1) พัฒนาเป้าหมายเครือข่ายเพื่อพัฒนาการศึกษาเชิงพื้นที่แบบมีส่วนร่วม 2) สร้างความเข้าใจบทบาทภาคีเครือข่ายของทุกภาคส่วนเพื่อพัฒนาการศึกษาเชิงพื้นที่ 3) พัฒนาศักยภาพบุคลากรทางการศึกษาให้มีเครือข่ายตามบริบทพื้นที่ 4) พัฒนาระบบการนิเทศหนุนเสริมการมีเครือข่ายเพื่อพัฒนาคุณภาพการศึกษาเชิงพื้นที่ และ 5) จัดเวทีประชาคมเพื่อแลกเปลี่ยนนวัตกรรมการพัฒนาคุณภาพการศึกษาเชิงพื้นที่ และ 3. การสร้างเครือข่ายการเรียนรู้ของครูสังคมศึกษาเพื่อพัฒนาคุณภาพการศึกษาผู้เรียน ประกอบด้วยครูสังคมศึกษา ผู้บริหารสถานศึกษา ผู้บริหารการศึกษา ศึกษานิเทศก์ คณาจารย์ในสถาบันการผลิตครู นักวิชาการศึกษา และชุมชน ได้รวมกลุ่มเพื่อสร้างเครือข่ายช่วยเหลือเกื้อกูล แบ่งปันความรู้และทรัพยากรโดยมีเป้าหมายในการพัฒนาคุณภาพการศึกษาเชิงพื้นที่ สำหรับข้อเสนอแนะจากการวิจัย คือ การสร้างเครือข่ายการเรียนรู้ในสถานศึกษาได้เปิดพื้นที่ให้ชุมชน องค์กรภาคประชาสังคม และสถาบันการผลิตครูในพื้นที่ได้เข้ามามีส่วนร่วมในการกำหนดแนวปฏิบัติที่ดีเพื่อใช้ทรัพยากรร่วมกันในทุกภาคส่วนสู่การพัฒนาคุณภาพการศึกษาผู้เรียนในโรงเรียนมัธยมศึกษา คำสำคัญ : กลยุทธ์  เครือข่ายการเรียนรู้  ครูสังคมศึกษา  คุณภาพการศึกษาผู้เรียน      This research aims to: (1) analyze the context that reinforces the construction of learning networks of social studies teachers in secondary schools; (2) propose strategies to drive the learning networks of social studies teachers to improve quality in education for learners in secondary schools; and (3) construct a learning network of social studies teachers to improve quality in education of secondary schools learners. The study was conducted by using qualitative methodology. The target groups were selected from 37 voluntary and purposive groups. According to the research finding results, the context that reinforces the learning network consists of three aspects: 1) the availability of learning networks; 2) network activities; and 3) network management. The driving strategic learning network consists of five aspects: 1) to develop network goals for the participation of area-based education development; 2) to construct an understanding of roles for a group network of all sectors of area-based education development; 3) to develop the potential of educational personnel to have a network in the context area; 4) to develop a supervision system for the set-up of a network to develop area-based quality education; and 5) to organize a civil society forum to share innovations to develop area-based quality education. A learning network development of social studies teachers to improve quality in education of learners involves social studies teachers, school directors, educational administrators, supervisors, instructors, educators and communities to cultivate a supportive network that can share knowledge and resources with the goal of quality improvement in area-based education. This research study suggests learning network construction in schools to support learning spaces in the community and civil society. Local area teacher institutes can participate using best practice guidelines to share educational resources in all aspects and so improve quality in the education of secondary schools learners. Keywords: Strategic, Learning Networks, Social Studies Teacher, Quality in Education of Learner